The capacity of organizations to deliver effective water management through the provisions of the Water Framework Directive: the case of Malta - Xerri, Francesca (Cranfield University, 2016)
Effective implementation of the European Water Framework Directive (WFD) is dependent on Member States’ national water institutions and organizations, often designated as ‘competent authorities’. Although substantial research relating to the Directive itself has been carried out, less is known about the extent to which competent authorities have the organizational capacity to deliver it. The literature notes that conceptual understanding of capacity has been hampered by lack of definitional clarity making both its management and assessment challenging. In this contribution, several conceptualizations of organizational capacity found in the literature are used to construct a set of core qualitative organizational components that encourage analysts to consider the ways in which legal authority, information and knowledge, skills, resources and leadership shape a competent authority’s ability to deliver the WFD. Malta, the smallest European Member State, is the case study used to test the application of these components. Qualitative empirical data collected from policy documents, face-to-face semi-structured interviews and online news media articles, provided the evidence to thematically explore and evaluate the Maltese competent authorities’ organizational capacity across the implementation of three main WFD provisions that are in focus: Article 8, 9 and 14. As a result, the core components of organizational capacity are expanded and refined to produce an organizational capacity thematic map. The results show that competent authorities experience influences across the institutional frameworks they work in as well as external factors (primarily political). The results also support the idea of the organizational capacity components being highly interlinked and the presence (or lack thereof) of one component having knock-on effects on others within an organization. The combination of these two factors highly affect management options and outcomes in the implementation of the WFD. In the small state context of Malta these highlight the need to channel support in a coordinated manner from European counterparts to the Maltese water network. In turn, the water network can have positive knock-on effects on the organizational capacity of the Maltese competent authorities, which currently struggle to perform and seize available opportunities due to low possession of human resources and time availability. The approach and findings presented in this research provide a mechanism and evidence base that can facilitate bilateral discussions between Member States as well as with the European Commission, and help inform the WFD review process planned by end of 2019.
Keywords: European Commision; competent authorities; organizational capacity profile; organizational institutionalism; qualitative thematic mapping; water governance